2015
DOI: 10.1007/s10995-015-1838-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Models for Characterizing Disparities in Exclusive Breastfeeding Performance in a Multi-ethnic Population in the US

Abstract: Findings underscore the importance of educational, clinical, and social support to promote XBR in mothers with sociodemographic factors predictive of none or poor XBR outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Both higher maternal education and maternal IQ were associated with a greater likelihood of breastfeeding initiation. It is well established that maternal education is tied to breastfeeding in the general population, [20][21][22][23][24][25] but the impact of maternal IQ has not been well studied. This prospective cohort demonstrated that maternal IQ has an independent influence on breastfeeding initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Both higher maternal education and maternal IQ were associated with a greater likelihood of breastfeeding initiation. It is well established that maternal education is tied to breastfeeding in the general population, [20][21][22][23][24][25] but the impact of maternal IQ has not been well studied. This prospective cohort demonstrated that maternal IQ has an independent influence on breastfeeding initiation.…”
Section: Discussionmentioning
confidence: 99%